Running Water in India's Cities : A Review of Five Recent Public Private Partnership Initiatives - World Bank (Washington, DC, 2014)
India is home to more than 370 million people in urban areas. No city in the country meets the government's targets for continuous pressurized safe water with full coverage and full cost recovery. Groundwater sources are also being depleted putting severe constraints on economic development. To make up for unreliable services, households have invested significantly in alternate arrangements over the past three decades. Reliable estimates of asset condition and performance in Indian cities are difficult to establish, given the poor culture of documentation, data collection, and reporting. Data drawn from several benchmarking initiatives indicate the following: service delivery parameters are well below established norms, with coverage through piped water supply ranging between 55 percent and 89 percent, and while per capita availability is fairly high, at 90-120 liters per day, no city offers continuous water supply. Daily supply averages four hours, with many cities alternating supply every other day. These challenges occur in a context of limited data or data management capability and largely unknown conditions of existing assets, which present difficulties in assessing the costs and timelines involved in improving service levels and operational efficiencies. Moreover, the investments required are likely to be significant, particularly since most cities have seen little systematic investment in asset management and expansion over the years. Simultaneously, it is recognized that investments alone will not be effective in the context of complex and fragmented institutions with little accountability; lack of capacity to run utilities efficiently and meet performance standards; weak commercial orientation; interference in utility operations by external entities; and the absence of a regulatory framework focused on customer service and financial sustainability